2010
DOI: 10.1007/s13353-010-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flavonoid pigments on the accumulation of fumonisin B1 in the maize kernel

Abstract: Mycotoxins are secondary metabolites with potential dangers for animal and human health. In particular, maize (Zea mays L.) infection caused by Fusarium and the consequent fumonisin contamination is widespread in several countries such as Italy. We developed six maize populations differing in their constitution of regulatory genes able to accumulate respectively anthocyanins in the aleurone layer (r1 gene), pericarp (b1 and pl1 genes) and phlobaphene in the pericarp (p1 gene). These coloured populations, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
(45 reference statements)
1
30
1
1
Order By: Relevance
“…Preliminary results indicated that phlobaphene pigments could be associated with a reduced level of mycotoxin contamination, in particular a reduction in fumonisin B1, in maize kernels, as reported in our previous paper 15 .…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Preliminary results indicated that phlobaphene pigments could be associated with a reduced level of mycotoxin contamination, in particular a reduction in fumonisin B1, in maize kernels, as reported in our previous paper 15 .…”
supporting
confidence: 82%
“…Preliminary data had shown the role of phlobaphenes and other flavonoids accumulated in maize pericarp on the reduction of fungal ear rot and fumonisins accumulation 15,33 . The phlobaphenes and other secondary metabolites are accumulated in many ancient landraces traditionally cultivated in the Padana Plane and in mountainous regions of Northern Italy 29,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Maize genotypes were originally in W22 background, homozygous dominant for the a1, a2, c1, c2, bz1 and bz2 genes, homozygous recessive for the r1 gene and different b1 pl1 constitution. To obtain cyanidin-rich and cyanidinfree corn with an isogenic background, a maize cyanidinrich hybrid was used carrying the B1 and Pl1 alleles (Red diet, RD), which confer purple pigmentation in seed pericarp and all plant tissues [41][42][43][44] . Plant and seed tissues carrying b1 pl1 alleles are cyanidin-free (Yellow diet, YD).…”
Section: Maize Productionmentioning
confidence: 99%
“…The presumable cause of the reduced flavone/flavanol content was the plant defense mechanisms as it was concluded in the case of winter wheat (Buśko et al, 2014). Alternatively, the flavonoids took part in the reaction to quinine inhibitor and the reduction of the level of FB1 in the pericarp (Pilu et al, 2011). Moreover, other polyphenols were increased in their concentration at the same time as the total polyphenol concentration did not change significantly.…”
Section: Discussionmentioning
confidence: 81%
“…The relationships between the resistance and the mycotoxin production have been well documented (e.g. Pilu et al, 2011). The resistance to Fusarium spp.…”
mentioning
confidence: 99%